Improving Students Speaking Ability Using Story Telling Methods in Class XI IPA SMAN 5 Kundur - Maulana, Aldi Hardian; Azis, Astuti (Universitas Terbuka, 2024)
One of the main goals of improving students’ engagement in speaking class is using certain strategies that are believed to expose a wide range of vocabulary and sentence structures. In this case, a teacher could use storytelling to assist students to express ideas more clearly and creatively. However, students of class XI IPA SMA Negeri 5 Kundur academic year 2023-2024 appeared to have low speaking skills. In this class, the level of speaking skill mastery is less than 50%. For this reason, the researchers teach narrative text using storytelling. This is a Classroom Action Research which was conducted in two cycles starting from April to May 2023. The research uses several instruments including observation, questionnaire, practice, and documentation. Data was analyzed quantitatively and the overall result of the research showed an increase in students’ mastery criteria up to 78,85%. This means that the storytelling method in teaching narrative text is effective in improving students’ speaking ability.